THE EFFECTIVENESS OF THE READING ALOUD METHOD IN IMPROVING FIFTH-GRADE STUDENTS’ SHORT STORY READING SKILLS - Perulu, Marnex (Journal Of Educational Experts (JEE), 2026)
Reading comprehension is a fundamental skill that must be mastered by elementary school students, particularly in understanding literary texts such as short stories. However, classroom practices in elementary schools often reveal persistent challenges, including students’ limited ability to comprehend texts, identify narrative elements, and retell story content effectively. This study aims to examine the effect of the reading aloud method on improving short story reading skills among fifth-grade students at SD Negeri 2 Tiakur. A quantitative approach with a quasi-experimental design was employed by implementing the reading aloud method in reading instruction. The research subjects consisted of fifth-grade students selected through purposive sampling. Data were collected using a short story reading skills test and analyzed through inferential statistical techniques. The findings indicate that the reading aloud method has a significant effect on enhancing students’ reading skills, particularly in terms of reading comprehension, pronunciation accuracy, intonation, and the ability to retell story content. These results suggest that reading aloud not only improves technical aspects of reading but also fosters students’ cognitive and affective engagement in the learning process. Therefore, the reading aloud method is recommended as an effective instructional strategy for improving short story reading skills in elementary school settings.